Expert Python Programming : Become a Master in Python by Learning Coding Best Practices and Advanced Programming Concepts in Python 3.7 - Jaworski, Michał; Ziadé, Tarek (Birmingham : Packt Publishing, Limited, 2019)
Expert Python Programming, Third Edition is a collection of valuable tips that will help you build robust and scalable applications in Python. These will help you become confident at solving challenging programming problems effectively.
Supplemental data types and containersSpecialized data containers from the collections module; Symbolic enumeration with the enum module; Advanced syntax; Iterators; Generators and yield statements; Decorators; General syntax and possible implementations; As a function; As a class; Parametrizing decorators; Introspection preserving decorators; Usage and useful examples; Argument checking; Caching; Proxy; Context provider; Context managers -- the with statement; The general syntax and possible implementations; As a class; As a function -- the contextlib module
Functional-style features of Python
Includes index.
Print version record.
eBooks on EBSCOhost
Keywords: Python (Computer program language); Application software -- Development; Python (Langage de programmation); Logiciels d'application -- Développement.; Application software -- Development; Python (Computer program language)